Time-evolution of ScCO2-weakened coal integrity: Chemo-hydromechanical coupling and geological sequestration implications - Peng Liu; Jingtao Yang; Baisheng Nie; Ang Liu; Wei Zhao; Hao Xu; Hengyi He (International Journal of Mining Science and Technology, 2025)
Geological sequestration of CO2 is critical for deep decarbonization, but the geomechanical stability of coal reservoirs remains a major challenge. This study integrates nanoindentation, XRD/SEM-EDS chemo physical characterization and 4D CT visualization to investigate the time-evolving mechanical degradation of bituminous coals with ScCO2 injection. The main results show that 4 d of ScCO2 treatment caused 50.47%–80.99% increase in load–displacement deformation and 26.92%–76.17% increase in creep depth at peak load, accompanied by 55.01%–63.38% loss in elastic modulus and 52.83%–74.81% reduction in hardness. The degradation exhibited biphasic kinetics, characterized by rapid surface-driven weakening (0–2 d), followed by stabilized matrix-scale pore homogenization (2–4 d). ScCO2 preferentially dissolved carbonate minerals (dolomite), driving pore network expansion and interfacial debonding, while silicate minerals resisted dissolution but promoted structural homogenization. These coupled geochemical-mechanical processes reduced the mechanical heterogeneity of the coal and altered its failure modes. The results establish a predictive framework for reservoir stability assessment and provide actionable insights for optimizing CO2 enhanced coalbed methane recovery.